A critical review of research relating to the learning, use and effects of additional and multiple languages in later life. (October 2019) - Pfenninger, Simone E.; Singleton, David
Abstract: While there is a growing body of research on second language acquisition (SLA) in children, adolescents, young and more mature adults, much remains to be explored about how adults in later life learn a new language and how good additional language learning is forthem . Our goal in this article is to survey and evaluate what is known about the linguistic, socio-affective, neurobiological and cognitive underpinnings of the second language (L2) learning process in older individuals, the extent to which L2 acquisition may be seen as contributing to healthy and active ageing, and how these phenomena are to be approached scientifically, methodologically and pedagogically. Our view is that a developmental enterprise as complex as L2 learning in senior adulthood and its effects in later life cannot be explained by a single theory or set of principles. Furthermore, we take it that L2 acquisition in the third age needs to be regarded not just as a goal in itself but as a means of promoting social interaction and integration, and that it is partly through the stimulation of social well-being that its cognitive effects may potentially be observed.